ENVIRONMENTAL PROPERTIES OF GALAXIES AT Z < 0.1 FROM THE SDSS VIA THE VORONOI TESSELLATION - Dobrycheva, D. V.; Melnyk, O. V.; Vavilova, I. B.; Elyiv, A. A. (Одеські астрономічні публікації, 2014)
The aim of our work was to investigate the environmental density of galaxies fromthe SDSS DR9 at z < 0.1 using the 3D Voronoi tessellation. The inverse volume of the Voronoi cell was chosen as a parameter of local environmental density. We examined a density of given bright galaxy taking into account its faint satellites located in the Voronoi cell. We found that with the increase of total galaxy density around the central bright galaxy, the probability that it has the early type is increasing.